A CGE analysis of the implications of technological change in Indian agriculture - Ghosh, J.; Shiferaw, K.; Sahoo, A.; Gbegbelegbe, Sika (Partnership for Economic Policy, 2016)
A recursive dynamic computable general equilibrium (CGE) model is used to conduct an exante analysis of the economy-wide impacts of new agricultural technologies in India. Differential impacts of changes in productivity of new promising cultivars for irrigated and rainfed maize and wheat are incorporated in the model. Technological change in these crops results in higher future economic growth as well as food security, both in food consumption and availability. While there is considerable scope for increasing the production of both crops through the introduction of new technologies, maize (both irrigated and rainfed) with promising cultivars for higher yield gain generates significant growth in output. The projected gains for wheat are primarily in the rainfed wheat output as this is where the yield gaps are highest from the promising technologies. Lower prices, particularly for maize and wheat, stimulate higher consumption of these cereals and other food commodities. Rural households benefit more than their urban counterparts in food consumption. Although maize’s contribution to the national economy is less than wheat, given the relatively higher estimated yield gains from promising maize technologies, the positive impacts of maize technologies on food security and national income are higher than the impacts of wheat. In view of the land and water constraints in Indian agriculture, maize which is predominantly rainfed and widely adapted could be a viable alternative for the future. However, a joint improvement of maize and wheat productivity would further enhance economic conditions and food security in India.